Staging Revolution: Form and Violence in La noche de los asesinos - Beltrán, Gina (Latin American Theatre Review, 2015)
Written within the first years of the Cuban revolution, José Triana’s La noche de los asesinos (1965) has traditionally been read as either a revolutionary or an antirevolutionary play. This article argues that more than its historical and political context, revolution constitutes La noche’s form. The concept of revolution as a violent, paradigm-shattering phenomenon relates to La noche’s shifting and unstable dramatic spaces. Triana creates a complex performative space that turns La noche into a dramaturgical exploration of revolution as violent change and transformation. Through Franz Fanon’s theoretical understanding of structural violence, this article ultimately investigates how La noche offers important insights into the experiential and emotional processes of the Cuban subject within the historical process of the revolution.